A Review of Commonly Used ‘Static’ and Dynamic Sensory Description Methods - ZHANG Zheting, YANG Aolin, XU Kunli, JIANG Kexin, MENG Fanyu, WANG Bei, JIANG Tao (Shipin Kexue, 2024)
The sensory characteristics of foods have become an important part of measuring the quality of foods, and the descriptive analysis of sensory characteristics is of great significance to the evaluation of the sensory characteristics of foods. Currently, the commonly used ‘static’ sensory descriptive methods include quantitative descriptive analysis (QDA) primarily based on expert panels, and the check-all-that-apply (CATA) and rate-all-that-apply (RATA) methods that are available for experts or consumers to profile the overall sensory characteristics of a product. However, the sensory characteristics of foods can change during consumption, so ‘static’ description methods are unable to fully and accurately represent the sensory characteristics of food products and their delicate changes. Therefore, dynamic sensory description methods such as temporal check-all-that-apply (TCATA), time intensity (TI), and temporal dominance of sensation (TDS), which more accurately and completely describe the sensory characteristics of food products, have attracted great attention. In this article, several common ‘static’ and dynamic sensory description methods and their applications are introduced in order to provide methodological guidance for research on the sensory characteristics of food products.